Modern Jewish cooking : recipes & customs for today's kitchen / Leah Koenig - Koenig, Leah
From a leading voice of the new generation of young Jewish cooks who are reworking the food of their forebears, this take on the cuisine of the diaspora pays homage to tradition while reflecting the values of the modern-day food movement. Author Leah Koenig shares 175 recipes showcasing handmade, seasonal, vegetable-forward dishes. Classics of Jewish culinary culture-- such as latkes, matzoh balls, challah, and hamantaschen-- are updated with smart techniques and vibrant spices. Approachable recipes for everything from soups to sweets go beyond the traditional, incorporating regional influences from North Africa to Central Europe. Featuring holiday menus and rich photography, this collection is at once a guide to establishing traditions and a celebration of the way we eat now